Volume 6: Turbomachinery, Parts A, B, and C 2008
DOI: 10.1115/gt2008-50560
|View full text |Cite
|
Sign up to set email alerts
|

Internal Losses and Flow Behavior of a Turbofan Stage at Windmill

Abstract: The flow through a high-bypass ratio fan stage during engine-out conditions is investigated, with the objective of quantifying the internal losses when the rotor is at “windmill”. An analysis of altitude test data at various simulated flight Mach numbers shows that the fan rotational speed scales with the engine mass flow rate. Making use of the known values of the nozzle coefficients, we deduce the stagnation pressure loss of the fan stage, which rises significantly as the mass flow rate increases. In order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 0 publications
7
35
0
Order By: Relevance
“…For the same tested engine in windmilling conditions, García Rosa et al (2015) state that stagnation pressure losses are encountered in the turbine-like mode zone along the fan stage, that is, for h/h max > 0.4. More specifically, the massive flow separations that develop on stator blades, around 60% span, widely contribute to losses, which is consistent with the conclusions of Prasad and Lord (2010). Finally all the profiles presented in Figure 3 show a fairly good self-similarity with respect to the range of tested inlet windmilling operating points.…”
Section: Steady Analysissupporting
confidence: 84%
See 2 more Smart Citations
“…For the same tested engine in windmilling conditions, García Rosa et al (2015) state that stagnation pressure losses are encountered in the turbine-like mode zone along the fan stage, that is, for h/h max > 0.4. More specifically, the massive flow separations that develop on stator blades, around 60% span, widely contribute to losses, which is consistent with the conclusions of Prasad and Lord (2010). Finally all the profiles presented in Figure 3 show a fairly good self-similarity with respect to the range of tested inlet windmilling operating points.…”
Section: Steady Analysissupporting
confidence: 84%
“…This effect is more pronounced close to the hub due to the meridional channel geometry (Figure 1). In windmilling, the inner sections of the fan operate in compressor mode, while the outer sections operate in turbine mode (Prasad and Lord, 2010;García Rosa et al, 2015). However, since the inlet flow is purely axial, the absolute velocity increases along the entire span.…”
Section: Steady Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The single windmill conditions of the S-engine mixed-flow compressor were simulated in Section 4.2. Figure 24 shows the distribution of relative Mach numbers around the rotor of an axial compressor from the previous study 2) and our S-engine mixed-flow compressor under single windmill conditions. As can be seen, flow separation on the pressure side is apparent both for the axial and mixed-flow compressor at a span of 80%, while there is no separation at a span of 40%.…”
Section: Comparison Between Axial and Mixed-flowmentioning
confidence: 99%
“…Prasad et al 2) studied a turbofan stage under windmill conditions and revealed that there is almost no influence and that a large total pressure loss occurs at the pressure side of both the rotor and the stator. Gill et al 3) investigated a multistage compressor under windmill conditions both by an experiment and a numerical simulation.…”
Section: Introductionmentioning
confidence: 99%